Representasi Kepribadian Remaja dalam Naskah Drama Temanku Sayang, Temanku Malang: Kajian Psikologi Erich Fromm: Penelitian - Kadir, Herson; Suleman, Fatma; M. Mulusi, Mirna; Hadji, Delvina; Eka Wahyuni Mohamad, Inayah; Febriana, Cindy (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study uses Erich Fromm's psychology theory, this study investigates the personality of adolescents in the drama script of Elsa Pebriyanti "My Dear Friend, My Poor Friend". The focus of the study is the existential conflict experienced by the main character, Ken, because of his parents' divorce. The method used is descriptive analysis, by looking at the dialogue and events in the script to reveal the identity crisis, basic human needs, and emotional responses of the characters. Ken shows in his interactions with his friends how important loving social support is to overcome the emotional difficulties of adolescents. This study emphasizes that building healthy social relationships is very important for adolescents to develop a stable and positive personality. These results are relevant for parents, educators, and the community to create an environment that supports the emotional development of adolescents.